Pengembangan Produk Kerajinan Kelompok Anyaman Mansiang Taratak Sejahtera dalam Rangka Meningkatkan Kinerja Pemasaran - Ratni Prima Lita; Henmaidi Henmaidi; Meuthia Meuthia; Devi Yulia Rahmi; Fatma Poni Mardiyah (Warta Pengabdian Andalas, 2021)
A business of Anyaman Mansiang in Taratak, Lima Puluh Kota Regency, West Sumatra Province has existed for a long time and is a hereditary business. One of the groups of craftsmen of this Mansiang leaf is the Sejahtera Group. The problems faced by partners are product development and lack of marketing performance. The purpose of this activity was to increase business growth, develop product competitiveness, accelerate technology and management diffusion from university to partners. In particular, the activity's objective was to develop mansiang leaf handicraft products in the Taratak Sejahtera woven mansiang group. The activity was carried out in 3 stages, namely the preparation stage, starting with socialization and obtaining permits with related institutions, contacting craftsmen to decide on the activity schedule and preparing activity modules, and preparing for the implementation of activities. The production aspect implementation stage used quality control methods, training methods on product variations, practical methods for tidying up products, training methods for product creation, and business consulting. At the monitoring and evaluation stage, activities were carried out to evaluate the implementation of activities and monitor the performance of activities. The activity results were related to quality control, increased product variety, increased product neatness and yarn that matches the color of the webbing, development of design innovation, and quality improvement to target the middle and upper segments. Mentoring activities need to be continued to help the business of the Taratak Sejahtera woven mansiang group continue to perform well.